Thomas Piketty, A Brief History of Equality. Colombia: Editorial Ariel, 2022. 294 pages. - Rosendo López-González; Astrid Ramírez-Valencia (Visión Electrónica, 2023)
Thomas Piketty, A Brief History of Equality